THE ROLE OF ART THERAPY IN DEVELOPING SOCIAL ADAPTATION SKILLS IN CHILDREN WITH DISABILITIES - Sultanova Jasmina Quatbay qizi (International Journal of Literature and Language Studies, 2026)
Social adaptation remains a major challenge for children with disabilities, especially for children with neurodevelopmental disorders such as autism spectrum disorder (ASD) and attention deficit/hyperactivity disorder (ADHD). This article examines the role of art therapy as a nonverbal, multisensory intervention aimed at improving social interaction, emotional regulation, and communication skills. Using a qualitative synthesis of modern literature and case studies, the study explores how the creative process bypasses language barriers and facilitates peer communication and self-development. The main findings show that art therapy significantly improves performance skills in the area of social interaction, reduces anxiety, and develops a sense of belonging through collaborative projects.